2023
DOI: 10.1021/acs.jpca.2c07197
|View full text |Cite
|
Sign up to set email alerts
|

Direct Elucidation of the Vibrationally Averaged Structure of Benzene: A Path Integral Molecular Dynamics Study

Abstract: Path integral molecular dynamics (PIMD) simulations for C 6 H 6 , C 6 D 6 , and C 6 T 6 have been carried out to directly estimate the distribution of projected C−H(D,T) bond lengths onto the principal axis plane. The average values of raw C−H(D,T) bond lengths obtained from PIMD simulations are in the order of ⟨R C−H ⟩ > ⟨R C−D ⟩ > ⟨R C−T ⟩ due to the anharmonicity of the potential energy curve. However, the projected C−H(D,T) bond lengths are almost the same as those reported by Hirano et al. [J . Mol. Struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…For example, several groups and we have reported that NQEs of hydrogen nuclei enhance the hydrogen bond strength and facilitate proton transfer reactions. [19][20][21][22][23][24] Furthermore, we have also demonstrated that considering the NQEs is indispensable for the analysis of the H/D isotope effects. 24 The NQEs of heavier atoms, such as carbon, have not been focused because their nuclei are much heavier than electrons.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…For example, several groups and we have reported that NQEs of hydrogen nuclei enhance the hydrogen bond strength and facilitate proton transfer reactions. [19][20][21][22][23][24] Furthermore, we have also demonstrated that considering the NQEs is indispensable for the analysis of the H/D isotope effects. 24 The NQEs of heavier atoms, such as carbon, have not been focused because their nuclei are much heavier than electrons.…”
Section: Introductionmentioning
confidence: 85%
“…[19][20][21][22][23][24] Furthermore, we have also demonstrated that considering the NQEs is indispensable for the analysis of the H/D isotope effects. 24 The NQEs of heavier atoms, such as carbon, have not been focused because their nuclei are much heavier than electrons. However, several recent studies have pointed out that the NQEs are also important when calculating the electronic structures of carbon atoms.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation